Comparison of Phototherapy Effect with and without Phenobarbital on the Newborns with Hyperbilirubinemia - Shah Farhat, Ahmad; saeidi, raza; Mohammadzadeh , Ashraf; Lotfi, Saeid Reza; hajipour, mahmoud (Iranian Journal of Child Neurology, 2024)
Objectives Jaundice occurs in 60% of full-term and 80% of pre-term newborns. This study compared the effect of phototherapy with and without phenobarbital on icteric newborns. Materials & Methods This study is a randomized clinical trial conducted from July until March 2018 at Imam Reza Hospital, Mashhad University of Medical Science, Iran. Full-term and near-term neonates with more than 2000 grams who were hospitalized in the mentioned period for jaundice were entered into the study. The newborns were divided into two groups using block randomization. Data were analyzed by SPSS version 19. Results The average gestational age was 36.4 weeks (SD 2.39) in the intervention group and 36.9 weeks (SD 2.16) in the control group, with no significant difference between them. The mean hospital stay for the intervention group was 72 hours (SD 1.66), compared to 55 hours (SD 1.88) for the control group. At discharge, the serum bilirubin level in the intervention group was 11.53 mg/dL (SD 0.77), while it was 10.80 mg/dL (SD 1.09) in the control group, a statistically significant difference. Conclusion According to this study, phototherapy with phenobarbital is not more effective than phototherapy alone in neonatal hyperbilirubinemia.